DESAIN ALAT UKUR SUHU DAN KELEMBABAN BERBASIS MIKROKONTROLER ATMEGA 16 - Talapessy, Ronaldo (PATTIMURA UNIVERSITY, 2012)
The has already designed temperature and humidity measurement devices using SHT11 sensor with display results in Liquid Crystal Display (LCD). Manually, the environmenttemperature was measured using a mercury thermometer and the environment humidity was measured by a hygrometer. The results were observed in analog and it often misread thus it caused errors in ready the data. To solve the problem, then were made a design temperature and humidity measuring devices digitally. The processor of this tool is ATMega16microcontroller that processes analog input signals to obtain a digital output. Temperature and humidity sensors SHT11 were used, the measurement results and read digital displayon the LCD. This design produced temperature and humidity measurement, aids accurately, it was ± 0.4 ° C and ± 3%.